Pusat Komunitas dan Kontestasi Memori Kolektif: Studi Kasus Ruang Publik Terpadu Ramah Anak (RPTRA) Kenanga di Cideng, Jakarta Pusat - Surayuda, Riena J. (Masyarakat: Jurnal Sosiologi, 2016)
Community center is a public space for the community that has a function for social activities, such as recreation and interaction, which in particular cases may diminish social problems. This study want to examines community center as Public Space and its memory collective to see the relevance of the theory and its significance to urban policy. The method of this article is qualitative using case study of Children-Friendly Integrated Public Space-Ruang Publik Terpadu Ramah Anak (RPTRA) Kenanga, Cideng, Central Jakarta. This article argues there has been a dysfunctional aspect that results in exclusiveness through collective memory contestation between the Government and Local Community. The study find that other than the changes from private property to public property, the establishment of RPTRA Kenanga creates new collective memory that has resulted in collective memory contestation between the government of DKI Jakarta and the local people, which led exclusivity in the public space.